Position paper: Telemedicine in occupational dermatology – current status and perspectives. (11th July 2018) - Elsner, Peter; Bauer, Andrea; Diepgen, Thomas Ludwig; Drexler, Hans; Fartasch, Manigé; John, Swen Malte; Schliemann, Sibylle; Wehrmann, Wolfgang; Tittelbach, Jörg
Summary: Teledermatology is the use of telecommunication technologies to exchange medical information for diagnosis, consultation, treatment and teaching in dermatology. While its use has been evaluated in a wide range of dermatological diagnoses, only few studies exist on its validity, diagnostic precision, feasibility, and cost‐effectiveness in occupational dermatology. However, these studies show a considerable potential for diagnosis, prevention, treatment support and follow‐up of patients with occupational skin diseases. Asynchronous (store and forward; SAF) or synchronous dermatology teleconsults could assist occupational medicine specialists not only in occupational preventive care, but also in the context of skin cancer screening in outdoor workers. Thus, teledermatology might contribute to earlier prevention and notification of occupational skin diseases. Modern smartphone apps with artificial intelligence technologies may also facilitate self‐monitoring in employees working in high‐risk jobs.